Determining the Use of Complementary and Alternative Medicine to Prevent Diabetic Foot Ulcer Levels in Patients with Type 2 Diabetes - Dincer, Berna; Akdeniz, Necmettin; Mete, Emel; Aksoy, Hasan; Kanat, Mustafa (GEVHER NESIBE JOURNAL OF MEDICAL AND HEALTH SCIENCES, 2022)
Objective: The aim of this article is to determine the use of complementary and alternative medicine (CAM) in patients with type 2 diabetes to prevent the formation of diabetic foot ulcer and to evaluate their level of knowledge and behavior about the diabetic foot. Material and Methods: A descriptive and cross-sectional study was performed in a research hospital in Istanbul with type 2 diabetes patients who used CAM and those who did not use. Diabetic foot care knowledge and behavior levels were assessed with Diabetes Foot Knowledge Questionnaire (DFKQ) and Foot Self-care Behavior Scale (FSCBS) questionnaire. Results: Of the 180 patients included in the study, 51.7% (n = 93) stated that they used CAM and 48.3% did not use CAM. Massage (21.5%), ozone oil (17.2%), hypericum perforatum oil (12.9%) and honey (10.8%) were the most preferred CAM in diabetic patients. The DFKQ and FSCBS scores were found significantly lower in CAM using group (p <0.05). Conclusıon: Diabetic patients who use CAM should be informed about the complications of such approaches that applied to diabetic foot. Therefore, evidence-based studies are necessary to investigate the benefits and possible adverse effects of these methods and to inform medical staff adequately